Y chromosome microdeletion and phenotype correlates with male infertility in Gujarati population - Shah, Parth S; Shah, Nidhi P; Shah, Sandip C; Patel, Tapan; Raval, Rutvik J; Dominic, Jeanny; Rao, Mandava V (Eastern Journal of Medical Sciences, 2020)
Background: Y chromosome microdeletions are one of the genetic causes of male infertility. Evaluation of this is important clinically to assist couple with such genetic defects using polymerase chain reaction-based sequence-targeted-site (STS). Objective: The objective of the study was to evaluate Yq microdeletion in suspected infertile male patients referred to our genetic center. Materials and Methods: European Association of Andrology STS markers for azoospermia factor (AZF) region were used to analyze these anomalies. In addition to semen analysis, cytogenetic, and hormonal studies have also been carried out using respective techniques. Results: Three of 41 cases (7.3%) included in our study had Yq microdeletion, of which one case was of azoospermia and two cases of severe oligozoospermia in AZFa and AZFc subregions were detected. Hormonal levels and karyotypes were unchanged. Conclusion: Yq microdeletion in our study exhibited is similar to Maharashtra, but it varies region-wise and ethnicity, including across Indian populations. Such couples require counseling before opting assisted reproductive technologies.